The potential of mushroom Baglog waste compost by adding FMA on ground water spinach (Ipomoea reptans Poir) growth - Adi Rastono; Masrur Muzadi; Hamzah Nata Siswara (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Unrecycled mushroom Baglog waste will become a place for spores to grow so that the spores will spread to the inoculation room, damaging the mushroom Baglog media, which causes crop failure. The right step for utilizing Baglog waste is composting it. A composted Baglog waste will be better if it is added with arbuscular mycorrhizal fungi (FMA), improving and increasing soil nutrient quality. This study aimed to determine the potential of mushroom Baglog waste compost by adding FMA to groundwater spinach growth (Ipomoea reptans Poir). This study used RAK to treat compost, compost+AFM 10g, compost+AFMA 20g, and compost+AFMA 30g. The study results indicate that Baglog waste compost and FMA have not been able to interact well on the parameters of tendril length, wet weight, and dry weight, as shown by the results that are not significantly different from compost treatment without FMA. Even so, compost waste has the potential to be used as fertilizer or media because it already has physical quality conforming to SNI. Adding FMA to mushroom Baglog waste compost is recommended because it can potentially increase plants' growth rate. The best interaction between Baglog mushroom waste compost and FMA was the compost + 10 g FMA treatment for all observation parameters.